Ceramic slurry, porous ceramic as well as preparation method and application of porous ceramic
By using polyethylene glycol as a pore-forming agent and specific process treatment, the complex problem of injection molding of alumina porous ceramics in the prior art was solved, and porous ceramics with high porosity, compressive strength and excellent insulation properties were prepared, which extended the service life of the material.
Patent Information
- Application Number
- CN202510011536.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-04
- Publication Date
- 2025-04-18
AI Technical Summary
The existing alumina porous ceramic injection molding technology has complex processes and is difficult to prepare porous ceramic materials with specific properties, which limits its widespread use.
Polyethylene glycol is used as the pore-making agent, combined with specific glue discharge and sintering processes, porous ceramics with large porosity, compressive strength and low carbon residue are prepared.
The high porosity, compressive strength and excellent insulation properties of porous ceramics are achieved, extending the service life of the material and avoiding the problem of yellowing and blacking.
Smart Images

Figure CN119841661A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and more specifically, to a ceramic slurry, porous ceramics, and a preparation method and application thereof. Background Art
[0002] Alumina ceramics have the advantages of high hardness, wear resistance, and good chemical stability. They are currently a widely used ceramic material. Alumina porous ceramics have a special pore structure inside. In addition to the advantages of ordinary ceramics, they also have the advantages of low density, light weight, large specific surface area, and low thermal conductivity. They are widely used in support, separation, filtration, sound absorption, sound insulation, carriers, and biosensors. In semiconductor chemical vapor deposition, sputtering, ion implantation, etching and other process processes, an electrostatic chuck with an alumina ceramic substrate and an electrode adsorbs, carries, and holds silicon wafers by electrostatic adsorption. Among them, alumina porous ceramics are installed in the gas through-holes on the ceramic substrate. In these processes, in order to avoid the temperature increase caused by plasma treatment of silicon wafers and to improve the temperature uniformity of the silicon wafer surface, inert gases such as helium are introduced into the back of the silicon wafer through the porous ceramics to improve the heat conduction between the silicon wafer and the ceramic substrate. In porous ceramics, a large number of pores act as heat conduction gas flow paths. According to the porosity and pore size of alumina porous ceramics, a suitable molding technology can be selected.
[0003] Porous ceramic injection molding is a new molding technology developed in recent years. It belongs to the near-net size molding technology. It can be used to prepare fine ceramic materials with high dimensional accuracy. It has the advantages of high mechanization and automation, and the molded products do not require machining or only require a small amount of machining. The injection molding process includes four steps: raw material mixing, injection molding, degreasing, and sintering. Among them, the first three steps are unique to injection molding and are also the three most critical steps that determine the performance of ceramic products. At present, the commonly used binder system for alumina porous ceramic injection molding technology is a plastic-based binder combined with a water-based binder and a wax-based binder. Although injection molding can prepare high-precision ceramic materials, its process flow is long and the equipment process is complex. It is difficult to prepare porous ceramic materials with specific properties, which to a certain extent limits its widespread use. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.
[0005] Another object of the present invention is to provide a ceramic slurry and a method for preparing a porous ceramic, wherein the present invention selects to use a polyethylene glycol pore former and a specific debinding and sintering process to prepare a porous ceramic with a larger porosity, a higher compressive strength and a lower carbon residue. The lower carbon residue forms a higher dielectric strength, so that the insulating properties of the porous ceramic are better.
[0006] In order to achieve these purposes and other advantages according to the present invention, the first aspect of the present invention provides an alumina ceramic slurry for electrostatic chuck porous ceramics, including 40-70wt% alumina ceramic powder, 35-50wt% pore former, 0.1-10wt% dispersant, 2-10wt% binder, 1-8wt% plasticizer, and 0-5wt% sintering aid, wherein the pore former is polyethylene glycol, and the molecular weight of the polyethylene glycol is 800-20000.
[0007] Preferably, the molecular weight of the polyethylene glycol is 2000-8000.
[0008] Preferably, the dispersant is at least one of ammonium polyacrylate, sodium polymethacrylate, ammonium polymethacrylate, ammonium citrate, and gum arabic, or a combination of two or more thereof.
[0009] Preferably, the binder is at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose, or a combination of two or more thereof.
[0010] Preferably, the plasticizer is one of glycerol, oleic acid, dibutyl phthalate, triethylene glycol acetate, dibutyl phthalate, and dioctyl phthalate.
[0011] Preferably, the sintering aid is at least one of magnesium oxide, silicon oxide, titanium oxide, zirconium oxide, yttrium oxide, and calcium carbonate, or a combination of two or more thereof.
[0012] The second aspect of the present invention provides a porous ceramic, including alumina ceramic slurry for electrostatic chuck porous ceramic, the carbon residue of the porous ceramic is 1 to 300 ppm, the porosity of the porous ceramic is 51 to 62%, and the compressive strength of the porous ceramic is 200 to 350 MPa.
[0013] A third aspect of the present invention provides a method for preparing a porous ceramic, comprising the following steps:
[0014] S1, 40-70wt% alumina ceramic powder, 35-50wt% pore former, 0.1-10wt% dispersant, 2-10wt% binder, 1-8wt% plasticizer, 0-5wt% sintering aid are mixed, heated and stirred to form a uniform slurry and degassing;
[0015] S2, using injection molding to inject the slurry into a mold, cool it, and demould it to obtain a green body;
[0016] S3, debinding and sintering the green body to obtain a porous ceramic sample.
[0017] Preferably, in step S1, the stirring speed is 1000-3000 rpm, the time is 8-15 hours, the degassing vacuum degree is -(0.1-100) kPa, and the heating temperature is 90-120°C.
[0018] Preferably, in step S1, the slurry is repeatedly heated 3 to 5 times while being stirred at a stirring speed of 200 to 300 rpm and a heating temperature of 80 to 100°C.
[0019] Preferably, the mixing equipment used in step S1 is one of a ball mill, a planetary mixer and a sand mill.
[0020] Preferably, in step S3, the debinding temperature is 450-650° C., the debinding time is 3-20 h, and the heating rate is 2-4° C. / min.
[0021] Preferably, in step S3, the sintering temperature is 1350-1650° C., the sintering time is 4-10 h, and the heating rate is 7-10° C. / min.
[0022] Preferably, in step S2, ethylene bisstearamide is coated inside the mold.
[0023] A fourth aspect of the present invention provides an electrostatic chuck comprising a porous ceramic.
[0024] The present invention has at least the following beneficial effects:
[0025] Using 35-50 wt% of polyethylene glycol as a pore-forming agent for alumina ceramic slurry can increase the porosity and compressive strength of porous ceramics and reduce carbon residues;
[0026] By using a reasonable porous ceramic preparation process, the carbon residue can be further reduced, and the yellowing and blackening of the porous ceramic material can be avoided. At the same time, the porosity and compressive strength can be increased, and the service life of the porous ceramic can be extended.
[0027] The low carbon residue forms a high dielectric strength, which makes the insulating performance of the porous ceramic better.
[0028] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the porous ceramic prepared in Example 1 of the present invention;
[0030] Figure 2 This is a scanning electron microscope image of the porous ceramic prepared in Example 2 of the present invention;
[0031] Figure 3 This is a scanning electron microscope image of the porous ceramic prepared in Example 3 of the present invention;
[0032] Figure 4 This is a scanning electron microscope image of the porous ceramic prepared in Comparative Example 2 of the present invention;
[0033] Figure 5 This is a scanning electron microscope image of the porous ceramic prepared in Comparative Example 3 of the present invention;
[0034] Figure 6 This is a scanning electron microscope image of the porous ceramic prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The first aspect of the present invention provides an alumina ceramic slurry for electrostatic chuck porous ceramics, comprising 40-70wt% alumina ceramic powder, 35-50wt% pore former, 0.1-10wt% dispersant, 2-10wt% binder, 1-8wt% plasticizer, 0-5wt% sintering aid, wherein the pore former is polyethylene glycol, and the molecular weight of the polyethylene glycol is 800-20000. Preferably, the molecular weight of the polyethylene glycol is 2000-8000. Polyethylene glycol is generally in the form of a flaky solid. The pore former is added to increase the porosity of the ceramic and expand the specific surface area. Selecting a suitable pore former can not only increase the porosity of the porous ceramic, but also make it have a higher compressive strength. The present invention uses polyethylene glycol as a pore former to obtain a porous ceramic with suitable porosity, compressive strength and carbon residue.
[0037] It should be noted that the binder and dispersant used in the present invention are aqueous solutions or water mixtures, and the proportions shown in the present invention are the actual usage of the binder and dispersant. When taking, the amount of aqueous solution or water mixture of the binder and dispersant to be taken is determined according to the actual demand for the binder and dispersant and the solid content label of the commercially available product. For example: 5g of dispersant is required, and the solid content of the commercially available product is 50wt%. 10g of dispersant solution is weighed and added to the slurry. Generally, the solid content of commercially available dispersants and binders is between 40 and 100wt%.
[0038] In an embodiment of the present invention, the alumina ceramic powder is a high-purity alumina ceramic powder, and the alumina ceramic powder is a high-purity alumina ceramic powder of more than 99.99%. Alumina has three main crystal types: α-Al2O3, β-Al2O3 and γ-Al2O3, and alumina is preferably an α-Al2O3 crystal type. The particle size of alumina is generally between 0.3 and 5 μm, preferably 1.5 to 3 μm, and the particle size of alumina needs to be uniform. If it is not uniform, the pore size of the prepared porous ceramic is uneven. Due to the uneven particle size of alumina, the porous ceramic structure is also uneven, so that the mechanical properties of different positions of the porous ceramic are different. During use, it is difficult to ensure uniform air permeability and the same use effect.
[0039] In an embodiment of the present invention, the dispersant is at least one of ammonium polyacrylate, sodium polymethacrylate, ammonium polymethacrylate, ammonium citrate, and gum arabic, or a combination of two or more thereof. The main function of the dispersant is to prevent the ceramic powder particles from agglomerating due to mutual attraction during the mixing and molding process, thereby causing uneven particle distribution and affecting the compactness and mechanical properties of the molded body. By using a dispersant, the suspension of the powder can be enhanced, thereby ensuring a uniform molding mixture.
[0040] In an embodiment of the present invention, the binder is at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose aqueous solution, or a combination of two or more thereof. The binder refers to an additive with a bonding effect added to the ceramic blank in order to improve the strength of the blank or prevent powder segregation. The binder is generally selected from substances that are easy to remove before sintering or during the sintering process.
[0041] In an embodiment of the present invention, the plasticizer is one of glycerol, oleic acid, dibutyl phthalate, triethylene glycol acetate, dibutyl phthalate, and dioctyl phthalate. The main function of the plasticizer is to improve the overall plasticity of the ceramic body, ensure that the body has a certain strength, and keep the body in its original shape before firing.
[0042] In an embodiment of the present invention, the sintering aid is at least one of magnesium oxide, silicon oxide, titanium oxide, zirconium oxide, yttrium oxide, and calcium carbonate, or a combination of two or more thereof. The sintering aid mainly functions to reduce the sintering temperature, increase the liquid phase, and improve the mechanical strength and chemical stability of the green body.
[0043] The second aspect of the present invention provides a porous ceramic. The porous ceramic of the present invention is prepared from alumina ceramic slurry for electrostatic chuck porous ceramics. The carbon residue of the porous ceramic is 1 to 300 ppm, the porosity of the porous ceramic is 51 to 62%, and the compressive strength of the porous ceramic is 200 to 350 MPa. The present invention uses 35 to 50 wt% of polyethylene glycol as a pore-forming agent for alumina ceramic slurry to prepare porous ceramics, which can increase the porosity and compressive strength of the porous ceramics and extend the service life. At the same time, it can also reduce carbon residue and avoid the porous ceramic material from turning yellow and black. The present invention adopts a reasonable debinding process and sintering process to control the porosity, compressive strength and carbon residue of the porous ceramic, so that the porous ceramic has a longer service life and excellent appearance.
[0044] A third aspect of the present invention provides a method for preparing a porous ceramic, comprising the following steps:
[0045] S1. 40-70 wt% alumina ceramic powder, 35-50 wt% pore former, 0.1-10 wt% dispersant, 2-10 wt% binder, 1-8 wt% plasticizer and 0-5 wt% sintering aid are mixed, heated and stirred to form a uniform slurry and defoamed.
[0046] The mixing equipment used in step S1 is one of a ball mill, a planetary mixer and a sand mill.
[0047] The stirring speed is 1000-3000 rpm, the time is 8-15 hours, the degassing vacuum degree is -(0.1-100) kPa, and the heating temperature is 90-120°C.
[0048] In order to make the slurry better mixed, the heated slurry can be cooled and then heated. The slurry is heated 3 to 5 times repeatedly, and stirred while heating. The stirring speed is 200 to 300 rpm and the heating temperature is 80 to 100 ° C. The stirring speed during the cooling and reheating process is low, which can reduce the amount of bubbles generated and remove bubbles more thoroughly during the degassing process.
[0049] The pore-forming agent is polyethylene glycol, and the molecular weight of the polyethylene glycol is 800 to 20,000; the polyethylene glycol is a flaky solid;
[0050] The dispersant is at least one of ammonium polyacrylate, sodium polymethacrylate, ammonium polymethacrylate, ammonium citrate, and gum arabic, or a combination of two or more thereof;
[0051] The binder is at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose aqueous solution, or a combination of two or more thereof;
[0052] The plasticizer is one of glycerol, oleic acid, dibutyl phthalate, triethylene glycol acetate, dibutyl phthalate, and dioctyl phthalate;
[0053] The sintering aid is at least one of magnesium oxide, silicon oxide, titanium oxide, zirconium oxide, yttrium oxide and calcium carbonate, or a combination of two or more thereof.
[0054] The dispersant and binder are aqueous solutions or water mixtures, and the water will be continuously removed during the heating process.
[0055] S2, using injection molding to inject the slurry into a mold, cool it, and demould it to obtain a green body;
[0056] In the present invention, the high temperature slurry in step S1 is cooled to 70-80° C. and then injected into a mold. The mold material is made of aluminum alloy, stainless steel, polyurethane, polytetrafluoroethylene, etc., preferably aluminum alloy and polytetrafluoroethylene;
[0057] When the mold is used, it needs to be heated to 70-80°C to prevent the slurry injected into the mold in step S1 from being suddenly cooled and solidified, so that the outer surface of the porous ceramic formed has uneven pore size and low porosity, and the outer surface performance of the porous ceramic is inferior to the inner part of the porous ceramic;
[0058] In a preferred embodiment of the present invention, ethylene bisstearamide is coated inside the mold to facilitate demoulding.
[0059] S3, debinding and sintering the green body to obtain a porous ceramic sample.
[0060] In step S3, the debinding temperature is 450-650°C, the debinding time is 3-20h, preferably 8-15h, more preferably 9-12h, and the heating rate is 2-4°C / min; in step S3, the sintering temperature is 1350-1650°C, preferably 1450-1650°C, the sintering time is 4-10h, preferably 5-8h, and the heating rate is 7-10°C / min.
[0061] The present invention utilizes the above-mentioned binder removal and sintering conditions to prepare porous ceramics, which can further reduce the carbon residue and prevent the porous ceramic material from turning yellow and black, while also increasing the porosity and compressive strength and extending the service life of the porous ceramics.
[0062] A fourth aspect of the present invention provides an electrostatic chuck, which comprises the porous ceramic prepared by the above preparation method.
[0063] The electrostatic adsorption technology used by electrostatic chucks is an advantageous technology that replaces traditional mechanical clamping and vacuum adsorption methods. It is widely used in semiconductors, panel displays, optics and other fields. The technical principle is that when an object with static electricity is close to another object without static electricity, due to electrostatic induction, the side of the object without static electricity close to the static electricity object will gather charges of opposite polarity to the charges carried by the charged object (the other side will generate the same number of charges of the same polarity). Since opposite charges attract each other, the "electrostatic adsorption" phenomenon will occur.
[0064] The porous ceramic in the embodiment of the present invention is used on a ceramic plate of an electrostatic chuck. The upper surface of the ceramic plate has a wafer mounting surface, and an electrostatic electrode and a heating electrode are built in. A plurality of through holes are provided on the ceramic plate. After being formed, the porous ceramic in the embodiment of the present invention is bonded inside the through holes to allow the inert gas to pass evenly.
[0065] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0066] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0067] <Example 1>
[0068] Weigh the raw materials according to the following mass percentages: 50% 99.99% pure aluminum oxide, 35% polyethylene glycol (PEG4000), 5% ammonium polyacrylate, 5% hydroxyethyl cellulose, 3% oleic acid, and 2% silicon oxide. Add the above components into a stirring tank and stir and mix them evenly in a blender. Stir at a speed of 1500 rpm, heat while stirring, heat to 90°C, heat and stir for 10 hours, and degas for later use.
[0069] The slurry is sucked and injected into an aluminum alloy mold by injection molding, and the mold is naturally cooled and molded, and then demolded to obtain a green body.
[0070] The green body is placed in an air furnace for debinding and sintering. The debinding heating rate is 4℃ / min, the temperature is raised to 580℃, and the debinding time is 10h. Then the temperature is raised to 1500℃ at a heating rate of 8℃ / min for sintering, and the heat preservation time is 6h. After cooling naturally to room temperature, a porous ceramic with complete external dimensions can be obtained. The scanning electron microscope image of the porous ceramic is as follows: Figure 1 shown.
[0071] <Example 2>
[0072] Weigh the raw materials according to the following mass percentages: 47% of 99.99% pure aluminum oxide, 38% of polyethylene glycol (PEG4000), 5% of ammonium polyacrylate, 5% of carboxymethyl cellulose, 3% of glycerol, and 2% of magnesium oxide. Add the above components to a stirring tank and place it in a blender to mix evenly. Stir at a speed of 1500rpm, heat while stirring, heat to 90°C, heat and stir for 10 hours, degas for use, and degas for use.
[0073] The slurry is sucked and injected into an alloy mold by injection molding, and the mold is naturally cooled and molded, and then demolded to obtain a green body.
[0074] The green body is placed in an air furnace for debinding and sintering. The debinding heating rate is 2℃ / min, the temperature is raised to 600℃, and the debinding time is 10h. Then the temperature is raised to 1600℃ at a heating rate of 9℃ / min for sintering, and the heat preservation time is 6h. After cooling naturally to room temperature, a porous ceramic with complete external dimensions can be obtained. The scanning electron microscope image of the porous ceramic is as follows: Figure 2 shown.
[0075] <Example 3>
[0076] Weigh the raw materials according to the following mass percentages: 45% 99.99% pure aluminum oxide, 40% polyethylene glycol (PEG4000), 5% ammonium polyacrylate, 5% carboxymethyl cellulose, 3% glycerol, and 2% magnesium oxide. Add the above components to a stirring tank and place it in a blender to stir and mix evenly. Stir at a speed of 1500rpm, heat while stirring, heat to 90°C, heat and stir for 10 hours, and degas. Repeat heating and cooling 3 times, with a stirring speed of 300rpm during heating and a heating temperature of 80°C, and degas.
[0077] The slurry is sucked and injected into an aluminum alloy mold by injection molding, and the mold is naturally cooled and molded, and then demolded to obtain a green body.
[0078] The green body is placed in an air furnace for debinding and sintering. The debinding heating rate is 2℃ / min, the temperature is raised to 600℃, and the debinding time is 10h. Then the temperature is raised to 1650℃ at a heating rate of 8℃ / min for sintering, and the heat preservation time is 6h. After cooling naturally to room temperature, a porous ceramic with complete external dimensions can be obtained. The scanning electron microscope image of the porous ceramic is as follows Figure 3 shown.
[0079] <Example 4>
[0080] Same as Example 1, except that ethylene bisstearamide is coated inside the mold when preparing the green body. The green body prepared by the present invention is easier to demould.
[0081] <Comparative Example 1>
[0082] The preparation method is the same as that of Example 1, except that the raw materials are weighed according to the following mass percentages: 50% 99.99% pure aluminum oxide, 35% starch, 5% ammonium polyacrylate, 5% polyvinyl alcohol, 3% glycerol, and 2% magnesium oxide.
[0083] <Comparative Example 2>
[0084] The preparation method is the same as that of Example 1, except that the raw materials are weighed according to the following mass percentages: 65% of 99.99% pure aluminum oxide, 20% of polyethylene glycol (PEG4000), 5% of ammonium polyacrylate, 5% of polyvinyl alcohol, 3% of glycerol, and 2% of magnesium oxide. Figure 4 As shown, porous ceramics are relatively dense in appearance.
[0085] <Comparative Example 3>
[0086] The preparation method is the same as that of Example 1, except that the raw materials are weighed according to the following mass percentages: 35% of 99.99% pure aluminum oxide, 50% of polyethylene glycol (PEG4000), 5% of ammonium polyacrylate, 5% of polyvinyl alcohol, 3% of glycerol, and 2% of magnesium oxide. Figure 5 shown.
[0087] <Comparative Example 4>
[0088] The preparation method is the same as that of Example 1, except that the binder removal temperature is 700°C, the binder removal time is 25h, and the heating rate is 5°C / min. Then the temperature is raised to 1700°C for sintering, the holding time is 12h, and the heating rate is 11°C / min.
[0089] <Comparative Example 5>
[0090] The preparation method is the same as that of Example 1, except that the debinding temperature is 800°C, the debinding time is 30h, and the heating rate is 7°C / min. Then the temperature is raised to 1800°C for sintering, the holding time is 15h, and the heating rate is 13°C / min. The scanning electron microscope image is shown in FIG. Figure 6 As shown, the heating rate in the debinding stage is too fast, and the gas generated by the thermal decomposition of organic matter in the green body cannot be discharged in time, resulting in defects such as cracks in the sintered samples, making it impossible to carry out relevant performance tests.
[0091] Table 1
[0092]
[0093]
[0094] As shown in Table 1, using a suitable amount of polyethylene glycol as a pore-forming agent can obtain porous ceramics with suitable porosity and compressive strength, less carbon residue, excellent air permeability, and not easy to crack. Such excellent performance can be well applied to the production of porous plugs on ceramic substrates in electrostatic chucks.
[0095] <Evaluation Method of Porous Ceramics>
[0096] 1. Porosity test
[0097] (1) Place the sample on a balance and weigh it. After the data stabilizes, read and record the dry empty weight m1;
[0098] (2) Place the sample in a vacuum infiltration machine, add pure water to completely immerse the sample, and evacuate the sample;
[0099] (3) Take the sample out of the water, wipe off the moisture on the sample surface, and then place the sample on a balance to weigh it. After the data stabilizes, read and record the saturated empty weight m2;
[0100] (4) Place the sample in an open container, which is placed on a special balance filled with water. After the data stabilizes, read and record the saturated water weight m3;
[0101] (5) The porosity is calculated by the testing software.
[0102] The calculation formula of porosity is: (m2-m1) / (m2-m3)*100%
[0103] 2. Compressive strength test
[0104] (1) Use a vernier caliper to measure and record the sample diameter;
[0105] (2) Place the sample in the middle of the loading head and start the compressive strength test procedure. After the test is completed, read and record the experimental data.
[0106] 3. Carbon residue test
[0107] (1) Place the sample in a special crucible for the carbon-sulfur analyzer and grind it into powder;
[0108] (2) Weigh the sample using a precision balance and add the corresponding flux;
[0109] (3) placing the crucible into a carbon-sulfur instrument through an automatic sample injector for high-temperature combustion;
[0110] (4) The generated CO2 gas is detected by a detector, converted into a carbon content reading and recorded.
[0111] 4. Dielectric strength test
[0112] (1) Measure the sample thickness;
[0113] (2) Place the sample in the test chamber, close the upper cover after the sample is in stable contact with the upper and lower electrodes;
[0114] (3) Set the maximum voltage to 50 kV, and read and record the breakdown voltage after the test is completed;
[0115] (4) Calculate dielectric strength (dielectric strength = breakdown voltage / thickness, unit kV / mm);
[0116] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. An alumina ceramic slurry for electrostatic chuck porous ceramics, characterized in that: The invention comprises 40-70wt% of alumina ceramic powder, 35-50wt% of pore former, 0.1-10wt% of dispersant, 2-10wt% of binder, 1-8wt% of plasticizer and 0-5wt% of sintering aid. The pore former is polyethylene glycol, and the molecular weight of the polyethylene glycol is 800-20000.
2. The alumina ceramic slurry for electrostatic chuck porous ceramics according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 2000-8000.
3. The alumina ceramic slurry for electrostatic chuck porous ceramics according to claim 1, characterized in that: The dispersant is at least one of ammonium polyacrylate, sodium polymethacrylate, ammonium polymethacrylate, ammonium citrate, and gum arabic, or a combination of two or more thereof; Preferably, the binder is at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose, or a combination of two or more thereof; Preferably, the plasticizer is one of glycerol, oleic acid, dibutyl phthalate, triethylene glycol acetate, dibutyl phthalate, and dioctyl phthalate.
4. The alumina ceramic slurry for electrostatic chuck porous ceramics according to claim 1, characterized in that: The sintering aid is at least one of magnesium oxide, silicon oxide, titanium oxide, zirconium oxide, yttrium oxide and calcium carbonate, or a combination of two or more thereof.
5. A porous ceramic, characterized in that: The invention comprises the alumina ceramic slurry for electrostatic chuck porous ceramics as described in any one of claims 1 to 4, wherein the carbon residue of the porous ceramics is 1 to 300 ppm, the porosity of the porous ceramics is 51 to 62%, and the compressive strength of the porous ceramics is 200 to 350 MPa.
6. The method for preparing the porous ceramic according to claim 5, characterized in that: The following steps are involved: S1, 40-70wt% alumina ceramic powder, 35-50wt% pore former, 0.1-10wt% dispersant, 2-10wt% binder, 1-8wt% plasticizer, 0-5wt% sintering aid are mixed, heated and stirred to form a uniform slurry and degassing; S2, using injection molding to inject the slurry into a mold, cool it, and demould it to obtain a green body; S3, debinding and sintering the green body to obtain a porous ceramic sample.
7. The method for preparing the porous ceramic according to claim 6, characterized in that: In step S1, the stirring speed is 1000-3000 rpm, the time is 8-15 hours, the degassing vacuum degree is -(0.1-100) kPa, and the heating temperature is 90-120° C.; In step S1, the slurry is repeatedly heated 3 to 5 times while being stirred at a stirring speed of 200 to 300 rpm and a heating temperature of 80 to 100°C.
8. The method for preparing the porous ceramic according to claim 6, characterized in that: In step S3, the debinding temperature is 450-650°C, the debinding time is 3-20h, and the heating rate is 2-4°C / min; in step S3, the sintering temperature is 1350-1650°C, the sintering time is 4-10h, and the heating rate is 7-10°C / min.
9. The method for preparing the porous ceramic according to claim 6, characterized in that: In step S2, ethylene bisstearamide is coated inside the mold.
10. An electrostatic chuck, comprising a porous ceramic prepared by the alumina ceramic slurry for electrostatic chuck porous ceramic according to claims 1 to 4 or the porous ceramic according to claim 5 or the method for preparing the porous ceramic according to any one of claims 6 to 9.